Selection of Humidification-Dehumidification (HDH) Desalination Technology for 3T Region: A Case Study in East Sumba - Maria Anindita Nauli; Angellie Naomi; Jansen Briano; Kathrisya Berlianie (G-Tech: Jurnal Teknologi Terapan, 2025)
Access to clean water remains a significant challenge in Indonesia’s Frontier, Remote, and Disadvantaged (3T) regions due to limited infrastructure and resources. One potential solution to address this challenge is the adoption of small-scale desalination systems. Among various available technologies, Humidification-Dehumidification (HDH) is considered promising for remote areas because of its operational simplicity, low investment costs, and compatibility with renewable energy sources. However, selecting the most appropriate HDH configuration requires careful evaluation across multiple criteria. This study aims to determine the most suitable HDH configuration for East Sumba Regency, a representative 3T region, by analyzing economic, technical, environmental, and social aspects. The Analytical Hierarchy Process (AHP) was used to compare four HDH system configurations: Closed Air Closed Water (CACW), Closed Air Open Water (CAOW), Open Air Closed Water (OACW), and Open Air Open Water (OAOW). Data were collected from published literature, and each configuration was assessed using a hierarchical decision-making model. The analysis found that the CAOW configuration ranked highest with a priority weight of 32.6%, primarily due to its superior maximum freshwater production (182 kg/hour) and the lowest freshwater cost (2.5 USD/m³) among the alternatives. The findings contribute to the development of data-driven decision-making frameworks for technology selection in under-resourced regions. This study provides practical insights for policymakers and engineers seeking sustainable and effective desalination solutions to improve clean water access in 3T regions, particularly East Sumba.